Carbon stock potential of agroforestry systems in low hills of north-western Himalayas - SHARMA, HARISH; PANT, K S; BISHIST, ROHIT; GAUTAM, K L; LUDARMANI; KUMAR, DHIRENDER (The Indian Journal of Agricultural Sciences, 2023)
The present experiment was conducted at Dr Y S Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh during 2019–21 to study the prevalent agroforestry systems and to assess their carbon stock potential. Sub-montane low hill zone of Chamba district of Himachal Pradesh was the study area with 15 farmers selected from each marginal, small and medium categories to carry out the study. Results of the investigation revealed that five agroforestry systems, viz. agrisilviculture, agrihorticulture, agrisilvihorticulture, silvopastoral and pastoralsilviculture were prevalent in the studied area. Maximum aboveground and belowground biomass production was recorded for the silvopastoral system among all the identified systems with least under pastoralsilviculture. Carbon stock potential among all the systems was recorded highest for the silvopastoral system (60.92 Mg/ha) and generally followed the order silvopastoral>agrisilvihorticulture>agrisilviculture>pastoralsilviculture>agrihorticulture. Farmer categories didn’t affect the carbon storage potential of the different agroforestry systems significantly. Soil carbon stock contributed more as compared to vegetation carbon stock with pastoralsilviculture having maximum soil:plant carbon ratio of 2.59. The study highlights the importance of the tree based land uses and offers the basis for selection of the potential system from the climate change mitigation point of view in the susceptible Himalayan region.